Long term effects of early life stress on HPA circuit in rodent models. (5th February 2021) - Babicola, Lucy; Ventura, Rossella; D'Addario, Sebastian Luca; Ielpo, Donald; Andolina, Diego; Di Segni, Matteo
Abstract: Adaptation to environmental challenges represents a critical process for survival, requiring the complex integration of information derived from both external cues and internal signals regarding current conditions and previous experiences. The Hypothalamic–pituitary–adrenal axis plays a central role in this process inducing the activation of a neuroendocrine signaling cascade that affects the delicate balance of activity and cross-talk between areas that are involved in sensorial, emotional, and cognitive processing such as the hippocampus, amygdala, Prefrontal Cortex, Ventral Tegmental Area, and dorsal raphe. Early life stress, especially early critical experiences with caregivers, influences the functional and structural organization of these areas, affects these processes in a long-lasting manner and may result in long-term maladaptive and psychopathological outcomes, depending on the complex interaction between genetic and environmental factors. This review summarizes the results of studies that have modeled this early postnatal stress in rodents during the first 2 postnatal weeks, focusing on the long-term effects on molecular and structural alteration in brain areas involved in Hypothalamic–pituitary–adrenal axis function. Moreover, a brief investigation of epigenetic mechanisms and specific genetic targets mediating the long-term effects of these early environmental manipulations and at the basis of differential neurobiological and behavioral effects during adulthood is provided. Highlights: Early life stress affects brain areas involved in HPA axis regulation. Early life stress induces different effects depending on manipulation and time window. Early life stress-induced alterations may result in long-term maladaptive outcomes.